Molecular Biotechnology - Basile, Giancarlo; SpringerLink (Online service) (New York : Springer US : Imprint: Humana Press.)
Molecular Biotechnology publishes original research papers on the application of molecular biology to both basic and applied research in the field of biotechnology. Particular areas of interest include the following: stability and expression of cloned gene products, cell transformation, gene cloning systems and the production of recombinant proteins, protein purification and analysis, transgenic species, developmental biology, mutation analysis, the applications of DNA fingerprinting, RNA interference, and PCR technology, microarray technology, proteomics, mass spectrometry, bioinformatics, plant molecular biology, microbial genetics, gene probes and the diagnosis of disease, pharmaceutical and health care products, therapeutic agents, vaccines, gene targeting, gene therapy, stem cell technology and tissue engineering, antisense technology, protein engineering and enzyme technology, monoclonal antibodies, glycobiology and glycomics, and agricultural biotechnology. Review articles on subjects in these areas are also welcome.
Keywords: Human genetics; Biotechnology; Biochemistry; Proteins; Cell biology; Biology -- Technique; Biotechnology; Biochemistry, general; Cell Biology; Protein Science; Biological Techniques; Human Genetics